Research in Adaptronic Automatic Control System and Biosensor System Modelling - Skopis, Vladimir; Uteshevs, Igors (Electrical, Control and Communication Engineering, 2015)
This paper describes the research on adaptronic systems made by the author and offers to use biosensors that can be later inserted into the adaptronic systems. Adaptronic systems are based, on the one hand, on the adaptronic approach when the system is designed not to always meet the worst condition, but to change the structure of the system according to the external conditions. On the other hand, it is an extension of common automatic control ad adaptive systems. So, in the introduction firstly the adaptronic approach and biosensor as a term is explained. Adaptive systems, upon which adaptronic ones are based, are also mentioned. Then the construction of biosensor is described, as well as some information is given about the classification of biosensors and their main groups. Also it is suggested to use lichen indicators in industry to control concentration of chemical substances in the air. After that mathematical models and computer experiments for adaptronic system and biosensor analysis are given.